Impaired insulin secretion predicting unstable glycemic variability and time below range in type 2 diabetes patients regardless of glycated hemoglobin or diabetes treatment - Miya, Aika (J Diabetes Investig, 2020)
AIMS/INTRODUCTION: To identify the coefficient of variation (CV) threshold for unstable glucose variability (GV) and hypoglycemia, and to characterize a patient population with unstable GV and hypoglycemia. MATERIALS AND METHODS: This was an observational study that enrolled 284 Japanese outpatients with type 2 diabetes who underwent continuous glucose monitoring. The C‐peptide index (CPI = [(fasting serum C‐peptide) / (plasma glucose)] × 100) was used as a marker of endogenous insulin secretion. The CV threshold between stable and unstable GV was defined as the upper limit of the CV distribution in the subgroup of patients who did not receive insulin nor insulin secretagogues (relatively stable GV subgroup, n = 104). The optimal CV range corresponding to time below target range ≥4% was determined for all patients using receiver operating characteristic curve analysis. Various characteristics of patients with unstable GV and hypoglycemia were extracted using multivariate logistic regression analysis. RESULTS: The upper limit of the CV in the relatively stable GV subgroup was 40. The optimal CV range corresponding to time below target range ≥4% was also defined as CV ≥40 (area under the curve 0.85) for all patients. The CPI was an independent risk for CV ≥40 (odds ratio 0.17, 95% confidence interval 0.04–0.50, P < 0.01). The optimal cut‐off point for CPI to predict a CV cut‐off value of 40 was equivalent to 0.81 (area under the curve 0.80). CONCLUSIONS: A CV of 40 discriminates unstable GV and hypoglycemia from stable GV in Japanese outpatients with type 2 diabetes. Impaired insulin secretion might affect the stability of GV.